Modeling Standardized Ileal Digestible Lysine to Calorie Ratio in 27- to 260-lb Genesus Finishing Pigs - Hilario M. Cordoba; Jamil E. G. Faccin; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
The first of two objectives of this study was to determine standardized ileal digestible (SID) Lys to calorie ratio (SID Lys:NE) for optimal performance of Genesus (Oakville, Manitoba, Canada) pigs from 27 to 260 lb. A second objective was to build a calculator tool to help nutritionists and producers when formulating diets with Genesus pigs. A total of 4,485 late nursery and 5,200 grow-finishing mixed-gender pigs were used in 4 and 5 studies, respectively. Studies were conducted by Genesus and results of these experiments were provided to the Kansas State University Applied Swine Nutrition Team for analysis and modeling. Diets from each trial were reformulated to obtain the dietary nutrient content using the NRC 2012 ingredient library. Growth performance and diet nutrient content were used in a Microsoft Excel spreadsheet to determine grams of SID Lys intake per kilogram of gain, SID Lys:NE, and NE intake. To select the optimum Lys level from each phase of the trials, ADG and F/G were evaluated. Regression equations for SID Lys per kilogram of gain, SID Lys:NE, and NE intake were generated by using the performance at the optimum Lys values in each phase. The equation for the optimal Lys:calorie ratio is: SID Lys:NE (g/Mcal) = -0.0112195247 × Average BW (lb) + 5.3408676477. The developed equations were then used to build the calculator tool available atwww.KSUswine.org. In conclusion, the results showed a quadratic response when calculating Lys intake per kilogram of gain and NE intake (kcal/d), and a linear response in the SID Lys:NE for pigs between 27 to 260 lb of BW. The calculator tool provides information about SID Lys requirements to formulate diets for maximum performance for Genesus pigs from 27 to 260 lb. Further research is needed to accurately estimate the SID Lys requirements of pigs beyond 260 lb.
Keywords: calorie ratios; SID lysine; finishing pigs; genetics